Dampak Kehadiran Wisata Religi terhadap Penghasilan Pedagang Makanan di Lingkungan Masjid Agung Syahrun Nur Sipirok - Jafar Nasution; Ali Hardana; Arti Damisa; Arbanur Rasyid (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
Customer interest is a high-value asset for banks, if customer interest increases, profits also increase. But in fact, customers complain about the services provided by the bank because it is not in accordance with customer expectations. The formulation of the problem in this study is whether there is an effect of product quality and service quality both partially and simultaneously on the interest of customers in PT Bank Syariah Mandiri Branch in Padangsidimpuan. The discussion of this research relating to product quality and service quality to customers is interesting. In connection with that, the approach taken is theories related to product quality, service quality, and customer interest. Service is any action or activity that can be offered by a party to another party, which is basically intangible and does not result in any ownership. This study uses a quantitative research approach, data collection techniques include questionnaires, with as many as 56 respondents as customers. The analysis used in this study is validity test, reliability test, descriptive analysis, normality test, linearity test, determination test (R2), multiple linear regression, t-test, and f test. The results obtained showed that the value of R Square was 0.785 or 78.5%. The T-test shows there is a significant influence between product quality on the interest of customers to save at PT. Bank Syariah Mandiri Padangsidimpuan Branch. Likewise, there is an influence between the quality of service to the interests of customers saving at PT. Bank Syariah Mandiri Padangsidimpuan Branch. The F test shows that simultaneously product quality and service quality have a significant effect on the interests of customers saving at PT. Bank Syariah Mandiri Padangsidimpuan Branch.South Tapanuli is one of the centers of regional tourism destinations, as evidenced by the increasing number of tourist visits in recent years. South Tapanuli is at the forefront of tourism business development, the tourism industry continues to increase. South Tapanuli also has a tourist destination that is interesting and has a great artistic value and cultural charm for the community. The results of this study can increase knowledge for researchers about how the economic impact on traders in the religious tourism area of the Syahrun Nur Sipirok Mosque. The type of research is qualitative research with a descriptive approach. The average gross income of traders in the Syahrun Nur Sipirok Grand Mosque area is quite high, which is between Rp. 15,000,000-Rp. 30,000,000 every month, only about 10% of labor salaries are issued by traders. The average labor salary is only Rp 1,500,000 per month. The payroll of workers whose amount is still below the South Tapanuli Provincial Minimum Wage (UMK) standard is IDR 2,903,042. The business that developed in the area of the Great Mosque of Syahrun Nur Sipirok was not only a food and beverage shop but there were other types of businesses that developed such as selling building tools, photocopying businesses, selling clothes and others. In the area of the Great Mosque of Syahrun Nur Sipirok there is a restaurant where the owner is non-Muslim.